THE EFFECT OF CASH FLOW ON COMPANY VALUE WITH PROFITABILITY AS AN INTERVENING VARIABLE IN MANUFACTURING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE YEAR 2020-2024 - Nurhalisa Nurhalisa; Nurman Nurman; Abdul Rahman (Universitas Negeri Makassar, 2026)
Abstract:This study aims to analyze the effect of cash flow on firm value with profitability as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. Firm value is measured using Price to Book Value (PBV), cash flow is proxied by cash flow from operating activities, and profitability is measured by Return on Equity (ROE). This study uses a quantitative approach with a causal design. The data used are secondary data from the company's annual financial statements selected through a purposive sampling technique, resulting in 10 companies as samples. Data analysis was performed using path analysis and the Sobel test to examine the direct and indirect effects between variables. The results show that cash flow has a positive and significant effect on profitability, profitability has a positive and significant effect on firm value, and cash flow has an indirect effect on firm value through profitability. However, cash flow does not have a direct effect on firm value. These findings demonstrate that profitability plays a mediating role in the relationship between cash flow and firm value. Therefore, increasing firm value is not only determined by the amount of cash flow, but also by the company's ability to manage that cash flow to generate profits.Keywords :Cash Flow; Profitability; Enterprise Value; Operating Activities; Price to Book Value (PBV) Ratio; Return on Equity (ROE).